2009
DOI: 10.1158/1078-0432.ccr-09-0582
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Recombinant NY-ESO-1 Protein Elicits Immunodominant HLA-DR52b-restricted CD4+ T Cell Responses with a Conserved T Cell Receptor Repertoire

Abstract: Purpose: ESO is a tumor-specific antigen with wide expression in human tumors of different histologic types and remarkable spontaneous immunogenicity. We have previously shown that specific T H 1 and antibody responses can be elicited in patients with no detectable preexisting immune responses by vaccination with rESO administered with Montanide ISA-51 and CpG ODN 7909. The purpose of the present study was to characterize vaccine-induced ESO-specific CD4 + Tcell responses. Experimental Design: We generated CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Whereas peptide ESO 123-137 was the minimal peptide optimally recognized by clonal CD4 + T cells, the ESO peptide originally used to identify the DR52b-restricted epitope was significantly longer, corresponding to the 25mer ESO 119-143 (9). We therefore synthesized DR52b/ESO 119-143 tetramers and assessed them on specific and control clonal populations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas peptide ESO 123-137 was the minimal peptide optimally recognized by clonal CD4 + T cells, the ESO peptide originally used to identify the DR52b-restricted epitope was significantly longer, corresponding to the 25mer ESO 119-143 (9). We therefore synthesized DR52b/ESO 119-143 tetramers and assessed them on specific and control clonal populations.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that more than 50% of ESO-specific DR52b-restricted CD4 + T-cell clones isolated from vaccinated patients use Vβ2, suggesting a highly restricted TCR repertoire for T cells recognizing this epitope (9). To directly assess Vβ2 usage by tetramer-positive cells, we costained the cultures with tetramers and anti-Vβ2 specific antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations